ANALYSIS AND MODELING OF ENVIRONMENTAL RADIATION IN CASCADE GOLOSIIVSKY OF PONDS - Кравець, М. О.; Кутлахмедов, Ю. О. (Science-based technologies, 2014)
Golosiyivsky forest , being , like any wood, as a barrier to the spread of pollution is the battery of various substances, including toxic. An integral part of the park is its Goloseevsky cascades. Golosiivsky rates undergo intensive eutrophication , due to the discharge of pollutants. Thus, at present there is an urgent need to study the ecological processes that occur in ponds. To do this we offer radionuclides as tracer, as the concentration of radionuclides such as 137Cs quite easily defined in reservoirs. It is known that 137Cs, is a chemical analog of important macronutrients for biota , K. and distribution of 137Cs, can be successfully used to study the distribution of pollutants like Pb, Zn and other heavy metals in the cascade of ponds . Purpose - to build a model of cascade golosiivskyi ponds and conduct its analysis. The base model Golosiivsky ponds (Didorivsky cascade) is based on flowcharts and takes into account the speed of transfer of radionuclides between the camera and inside each cell between water, biota and sediments. The analysis of the processes of distribution and redistribution radionuklides on components in the cascade , calculated assessment of radionuclides in the first and second rates of 20 and 40 years after the accident, the influence of the velocity of radionuclide transfer processes of distribution and redistribution of radionuclides between the first and second rates. As a result, we were able to adequately describe the behavior of ecosystems golosiivskyi cascade ponds.